The effects of work–family interface on domain‐specific satisfaction and well‐being across nations: The moderating effects of individualistic culture and economic development. Issue 4 (16th August 2018) - Xu, Shan; Wang, Yanling; Mu, Ren; Jin, Jiafei; Gao, Feiyi
Abstract: Work–family conflict (WFC) and work–family enrichment (WFE) have been shown to be important predictors of employees' domain‐specific satisfaction and well‐being. In this meta‐analysis, we consider how the effects of WFC/WFE on various outcomes differ across different national cultures and economic settings. We hypothesized that WFC would have stronger effects on employees' domain‐specific satisfaction and well‐being in high individualistic nations and economies with higher levels of economic development, whereas WFE would have stronger effects on employees' domain‐specific satisfaction and well‐being in low individualistic nations and economies with lower levels of economic development. Results generally supported these hypotheses, suggesting that employees in more individualistic and more developed countries are more sensitive to how work interferes with family life, whereas employees in less individualistic and less developed countries are more sensitive to how work provides material, social, and cognitive resources that help in the fulfillment of family roles. Further research is needed exploring more detailed explanations for these differences and their implications for spillover theory and work–family practices in organizations.